Identification and selection of suitable landfill sites using GIS-based multi-criteria decision analysis in the Peshawar District, Pakistan. Issue 3 (March 2023) - Ali, Iftikhar; Islam, Aneeza; Ali, Syeda Maria; Adnan, Syed
Managing municipal solid waste (MSW) is indispensable for public health and quality living standards in urban and rural environments. Suitable landfill site selection (LSS) requires the consideration of many diverse criteria. This study uses various environmental, social and economic criteria in a sophisticated multi-criteria decision analysis (MCDA) within the geographical information system (GIS) and aims to provide a scientific basis for the identification of suitable landfill sites which can efficiently be used for MSW in one of the most urbanized cities (Peshawar district) in Pakistan. The methodology involves pairwise comparisons of the selected and ranked criteria using the analytical hierarchy process (AHP). A weighted linear combination (WLC) was applied to generate the most suitable landfill site for MSW disposal within the study area. The results show that approximately 11.4% (14, 485.15 ha) and 16.6% (21, 211.95 ha) of the total study area are either very highly suitable or highly suitable, 20.8% (26, 525.56 ha) area is unsuitable and the remaining areas are either low (27.3%; 34, 834.84 ha) or moderately suitable (23.8%; 30, 356.84 ha) for the construction of landfill sites. It is recommended that using the proposed landfill sites would have the least consequences of public health risks and environmental degradation.